Comparative Analysis of the TRB Locus in the Camelus Genus - Antonacci, Rachele; Bellini, Mariagrazia; Linguiti, Giovanna; Ciccarese, Salvatrice; Massari, Serafina (Frontiers in Genetics, 2019)
T cells can be separated into two major subsets based on the heterodimer that forms their T cell receptors. αβ T cells have receptors consisting of α and β chains, while γδ T cells are composed of γ and δ chains. αβ T cells play an essential role within the adaptive immune responses against pathogens. The recent genomic characterization of the Camelus dromedarius T cell receptor β (TRB) locus has allowed us to infer the structure of this locus from the draft genome sequences of its wild and domestic Bactrian congeners, Camelus ferus and Camelus bactrianus. The general structural organization of the wild and domestic Bactrian TRB locus is similar to that of the dromedary, with a pool of TRBV genes positioned at the 5’ end of D-J-C clusters, followed by a single TRBV gene located at the 3’ end with an inverted transcriptional orientation. Despite the fragmented nature of the assemblies, comparative genomics reveals the existence of a perfect co-linearity between the three Old World camel TRB genomic sequences, which enables the transfer of information from one sequence to another and the filling of gaps in the genomic sequences. A virtual camelid TRB locus is hypothesized with the presence of 33 TRBV genes distributed in 26 subgroups. Likewise, in the artiodactyl species, three in-tandem D-J-C clusters, each composed of one TRBD gene, six or seven TRBJ genes, and one TRBC gene, are placed at the 3’ end of the locus. As reported in the ruminant species, a group of four functional TRY genes at the 5’ end and only one gene at the 3’ end, complete the camelid TRB locus. Although the gene content is similar, differences are observed in the TRBV functional repertoire, and genes that are functional in one species are pseudogenes in the other species. Hence, variations in the functional repertoire between dromedary, wild and domestic Bactrian camels, rather than differences in the gene content, may represent the molecular basis explaining the disparity in the TRB repertoire between the Camelus species. Finally, our data contribute to the knowledge about the evolutionary history of Old World camelids.